2016 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2016
DOI: 10.1109/icassp.2016.7472355
|View full text |Cite
|
Sign up to set email alerts
|

Non-cooperative cross-channel gain estimation using full-duplex amplify-and-forward relaying in cognitive radio networks

Abstract: In this paper, we propose a new estimation method to obtain the cross-channel gain, which avoids the severe interference to the primary receiver (PR) in existing relay-assisted estimation methods. In our method, we let the cognitive transmitter add a time delay when it conducts the full-duplex amplify-and-forward relaying. This forces the time-difference-of-arrival (TDOA) between the direct and relay signals to be large enough rather than randomly large or small. Then we develop our estimation method only in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, this approach may not be suitable for the scenarios causing large Time Difference of Arrivals (TDOAs) between the direct signal and the relayed signal since TDOA is a random variable and depends on the locations of the ST, PT and PR. To address this issue, authors in [141] proposed to introduce a time delay at the FD-based ST while performing AF relaying in order to force the TDOA to be large enough. Subsequently, an estimation algorithm was developed to estimate cross-channel gains in the large TDOA case and it has been shown that this delay-enabled method can precisely control the interference to the PR than the relay-assisted only approach.…”
Section: A Underlay Dss Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this approach may not be suitable for the scenarios causing large Time Difference of Arrivals (TDOAs) between the direct signal and the relayed signal since TDOA is a random variable and depends on the locations of the ST, PT and PR. To address this issue, authors in [141] proposed to introduce a time delay at the FD-based ST while performing AF relaying in order to force the TDOA to be large enough. Subsequently, an estimation algorithm was developed to estimate cross-channel gains in the large TDOA case and it has been shown that this delay-enabled method can precisely control the interference to the PR than the relay-assisted only approach.…”
Section: A Underlay Dss Networkmentioning
confidence: 99%
“…In this context, FD relaying-assisted estimator has been proposed in [121] and a delay-enabled method in [141] towards the improving the PUs protection. Furthermore, improper Gaussian signaling at the SUs has been shown to be advantageous in an underlay spectrum sharing problem under certain conditions [138].…”
Section: Summary and Insightsmentioning
confidence: 99%